Microseismic Signals in Heading Face of Tengdong Coal Mine and Their Application for Rock Burst Monitoring - JianJu Ren; Wenlong Zhang; Zheng Wu; Ji Li; Ying Shen (Shock and Vibration)
Microseismic (MS) monitoring is an important and commonly used geophysical method in coal mines to predict rock burst which has great influence on safety production. MS monitoring technology and analysis method of the whole mine or working face have been matured, but its use in heading faces of coal mine is not mature due to small disturbances and narrow layout spaces. To carry out MS monitoring and early warning in the heading face, signal recognition must be adequately performed first, and monitoring objects and indicators must be obtained. Through field tests of MS systems at the 117 track gateway of Tengdong coal mine, interference signals of equipment operation and effective signals of coal vibration are accurately collected. After analysis, the waveform characteristics, spectrum, and propagation distance of the interference signals and coal vibration signal are different. Some effective signals with small energy (one-channel triggering) cannot be used as early warning indicators because they are concealed by interference signals. Through trial operation, it is found that large energy (three-channel and four-channel triggering) coal vibration events successfully predicted a rock burst. The MS system of 117 track gateway of Tengdong coal mine should be able to remove the interference signals in real time through the algorithm and take the number of large energy coal vibration signal rather than all coal vibration events as the predictor for rock burst risk monitoring.